Badai Pasti Berlalu (The Storm Will Surely Pass) - Irwan Abdullah et all; Maylisa Oktavira (Graduate Program of Pontianak Institute of Islamic Studies, 2014)
The border is the outermost region of a country that borders neighboring countries. Indonesia, as an archipelagic country, has many regions directly bordered by neighbouring countries. Kalimantan, for example, the third largest island in the world and the largest in Indonesia, lies to the North of the Island of Java, and Sulawesi Island to the West. The island of Kalimantan is divided into areas of Brunei, Indonesia (two thirds) and Malaysia (one third).